Routes towards manufacturing biodegradable electronics with polycaprolactone (PCL) via direct light writing and electroless plating. (1st June 2022) - Abdulrhman, Mansour; Zhakeyev, Adilet; Fernández-Posada, Carmen M; Melchels, Ferry P W; Marques-Hueso, Jose
Abstract: The electronic industry has room for improvement in adopting cleaner strategies, both in production processes (often energy-intensive and polluting) and in waste management. Many small components like security tags are routinely disposed of via general waste, which could be reduced adopting biodegradable polymers. In this work, a method for selective deposition of metallic micro-tracks on polycaprolactone (PCL) for circuitry integration is presented. The polymer is biodegradable, flexible, suitable for 3D printing, and can be obtained from sustainable sources. Photoreduction of Ag ions was used to generate seeds for subsequent selective electroless copper (Cu) plating in a process that avoids common but undesirable compounds such as cyanides and palladium. Two different photopatterning methods were successfully used to achieve selective Cu plating: flood exposure with a 460 nm light-emitting diode (LED) and direct laser writing (DLW) using a 405 nm laser, achieving 47 ± 11 μ m wide tracks. The deposition of uniform Cu layers on PCL substrates is demonstrated, with thicknesses of up to 14 μ m and electrical conductivities of up to 2.06 × 10 7 S m −1, which is near the conductivity of bulk Cu (5.89 × 10 7 S m −1 ). Cu-plated interconnects were demonstrated to be fully functional for powering a 5 SMD LEDs circuit. Furthermore, DLW enabled the interconnect manufacturing on an uneven substrate. This method is flexible, selective, low-cost, vacuum-free and of minimized environmental impact, and it provides a new route towards the manufacturing of biodegradable electronics.